(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
This article examines the representation of female agency in workplace, and demonstrates how being biologically part of a particular group ‘female’ restrain your agency. It argues that workplace has restrained female agency by creating a new domesticity within the public sphere, where female employees have been outsourced or exploited by their male superiors. Put it simply, the article explains how workplace have privatized the domain of female employees, creating a new private sphere in workplace and reinforced female employees’ structure of power that should constitute their agency. It illustrates that while post-feminists have been occupied with the diversity on the managerial level and female intensive involvement in male-dominated career, they have been distracted from the way female agency has been violated in workplace.